2019
DOI: 10.1186/s13063-018-3168-4
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Vitiligous lesions Repigmentation after the Administration of Atorvastatin calcium salt and Simvastatin-acid sodium salt in patients with active vitiligo (EVRAAS), a pilot study: study protocol for a randomized controlled trial

Abstract: BackgroundVitiligo is a chronic skin disorder presenting with depigmentation, the pathogenesis of which is complex but the autoimmune theory is now preferred. Multiple immunologic processes, including stimulation of the T-helper (Th)1 response, formation of autoreactive melanocyte-specific CD8+ T lymphocytes, a decrease in the blood concentration of T regulatory (Treg) cells, and an increase in interleukin (IL)-17 and interferon (IFN) concentration, have been shown to contribute to vitiligo progression and mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…Simvastatin, a potent statin drug used widely in dyslipidemia and cardiovascular diseases, also possesses antioxidant and anti-inflammatory properties by its action on CD8+ T cells. It inhibits the production of proinflammatory cytokines, which is an important factor in the pathogenesis of vitiligo, as discussed above [10].…”
Section: Role Of Simvastatin As An Immunomodulator In Vitiligomentioning
confidence: 97%
See 2 more Smart Citations
“…Simvastatin, a potent statin drug used widely in dyslipidemia and cardiovascular diseases, also possesses antioxidant and anti-inflammatory properties by its action on CD8+ T cells. It inhibits the production of proinflammatory cytokines, which is an important factor in the pathogenesis of vitiligo, as discussed above [10].…”
Section: Role Of Simvastatin As An Immunomodulator In Vitiligomentioning
confidence: 97%
“…Simvastatin, a potent statin drug used widely in dyslipidemia and cardiovascular diseases, also possesses antioxidant and anti-inflammatory properties by its action on CD8+ T cells. It inhibits the production of pro-inflammatory cytokines, which is an important factor in the pathogenesis of vitiligo, as discussed above [ 10 ]. A small clinical trial conducted by Vanderweil et al found topical simvastatin to be more useful than the systemic form, citing potential adverse effects of the systemic form [ 33 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…With growing safety concerns regarding systemic simvastatin, a pilot randomized controlled trial is currently underway involving active vitiligo patients and topical atorvastatin calcium salt (1%) or simvastatin‐acid sodium salt (1%) over 12 weeks (Vitiligous lesions Repigmentation after the Administration of Atorvastatin calcium salt and simvastatin‐acid sodium salt in patients with active vitiligo [EVRAAS] trial). Currently, patients are being recruited for this study 39 …”
Section: Simvastatin In Vitiligo: Current Evidencementioning
confidence: 99%
“…[ 3 ] In patients with an active form, skin and blood is abundant with melanocyte‐specific, autoreactive CD8 + T cells which have an important role in depigmentation. [ 4 ] However, previous research has also shown a marked redox imbalance in keratinocytes obtained from the perilesional skin of patients with active disease (eg increase in reactive oxygen species production and lipoperoxidation). [ 5,6 ] One of the obstacles in the clinical management of vitiligo is the assessment of disease activity.…”
Section: Introductionmentioning
confidence: 99%